Right Hepatic and Portal Vein Embolization before Right Hepatectomy for Colorectal Cancer Liver Metastases - Eduardo E. Montalvo-Javé; Edwin A. Ayala-Moreno; Alejandro Rossano García; Alejandro Diaz Girón Gidi; Jorge Guerrero Ixtlahuac (Case Reports in Gastroenterology, 2023)
Colon cancer has had a significant increase in its incidence in recent years. Many of the cases are diagnosed late; it is not unusual that a large number of cases present metastatic disease at the time of diagnosis, and the liver is the main organ where these lesions occur. Surgical approach to this condition has undergone many advances which have allowed a better approach to them. Local techniques such as embolization have gained momentum in recent years and are a great help to the surgical planning. We present the case of a 72-year-old female patient diagnosed with colorectal cancer and metastatic disease. Multiple liver tumors were demonstrated by imaging studies. A staged resection of the primary tumor and the metastatic hepatic tumors was planned. It was decided to perform an embolization of the hepatic artery to cause hypertrophy of the left lobe before the second stage of the surgical approach with good clinical and laboratorial findings after the surgery. Follow-up with adjuvant chemotherapy, imaging studies and tumor markers is planned. Several publications state that surgical approach of metastatic disease is still controversial and that decisions should be made under the context of each patient. Many techniques have shown good results; embolization of the hepatic tumors has a good outcome in the survival rate in selected patients. Hepatic volume and future liver remnant should be always assessed with imaging studies. Each case has to be individualized for the approach of the metastatic disease, always in a coordinated teamwork for maximum benefit of the patient.